1976
DOI: 10.1136/gut.17.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Hyperamylasaemia after duodenoscopy and retrograde cholangiopancreatography.

Abstract: SUMMARY The salivary and pancreatic isoamylases of serum were determined separately in 234 cases ofduodenoscopy and retrograde cholangiopancreatography. Successful pancreatic opacification was associated with pathologically high pancreatic serum amylase activities in 60% of the cases.Extensive opacification was associated with large increases of pancreatic serum isoamylases, the maximal rise recorded was 40 times the initial value. In spite of these striking chemical events only two patients developed clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…Quantitation of the volume injected appears to be of limited clinical value, as contrast tends to spill into the duodenum. However, the greatest elevations of total serum amylase activity and the highest frequencies of elevation occurred after complete filling of the acini [57,58] . Skude et al [57] in a series of 219 patients reported that pancreatic enzyme level elevation after ERCP correlated directly with the extent of opacification of the pancreatic duct system.…”
Section: Contrast Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitation of the volume injected appears to be of limited clinical value, as contrast tends to spill into the duodenum. However, the greatest elevations of total serum amylase activity and the highest frequencies of elevation occurred after complete filling of the acini [57,58] . Skude et al [57] in a series of 219 patients reported that pancreatic enzyme level elevation after ERCP correlated directly with the extent of opacification of the pancreatic duct system.…”
Section: Contrast Mediamentioning
confidence: 99%
“…However, the greatest elevations of total serum amylase activity and the highest frequencies of elevation occurred after complete filling of the acini [57,58] . Skude et al [57] in a series of 219 patients reported that pancreatic enzyme level elevation after ERCP correlated directly with the extent of opacification of the pancreatic duct system. Increases in intraductal pressure and filling of side branches may result in leakage of the pancreatic secretions into the circulation.…”
Section: Contrast Mediamentioning
confidence: 99%
“…It is difficult to determine the exact time of the onset when the inflammation of the pan creas occurs. Serum levels of pancreatic enzymes repre sent rapid elevation after endoscopic retrograde pancrea tography [9][10][11] because this phenomenon is caused by a transient passage of pancreatic fluid into the bloodstream through the acinovenous pathway following a rapid and marked elevation of intraductal pancreatic pressure [10,12]. Therefore, no previous studies have demonstrated the alterations of serum levels of pancreatic enzymes dur ing the period from the beginning of increase in serum levels to the maximal levels.…”
Section: Discussionmentioning
confidence: 99%
“…ERCP causes hyperamylasemia in 20-70 % of examinations. Post-ERCP pancreatitis occurs in 1-7 % of patients, and is associated with increased morbidity and, occasionally, mortality [1][2][3][4]. Almost certainly, the aetiology of this type of pancreatitis is multifactorial.…”
mentioning
confidence: 99%